2010
DOI: 10.1002/ejic.200901145
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II), Copper(II), and Nickel(II) Complexes of Bis(tripodal) Diamide Ligands – Reversible Switching of the Amide Coordination Mode upon Deprotonation

Abstract: A series of dinuclear Zn(II), Cu(II) and Ni(II) complexes of two new bis-tripodal ligands with aromatic (H 2 -4a) and aliphatic (H 2 -4b) diamide spacers has been synthesized and structurally characterized. Each of the two tripodal entities of the neutral dinucleating ligands coordinates to one metal ion via three amine functions and a carbonyl oxygen atom of the amide groups. Either trifluoroacetate counterions or solvent molecules complete the trigonal-bipyramidal (Zn, 5a), square-pyramidal (Cu, 6a and 6b), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The synthetic paths to complex 5 emphasize metal exchange processes in intricate proton/metal competitions that are likely related to synthetic routes to metalloproteins and enzymes. Engagement of carboxamide oxygens as donor sites for zinc in peptide bioconjugates have been observed by the Alsfasser group, while Hahn et al., have reported a pH dependent, reversible switching of the N/O amide coordination modes in tripodal complexes of Zn II , Cu II , and Ni II . More closely related to our discovery are well‐designed studies via infrared multiple photon dissociation spectroscopy and DFT calculations from Dunbar et al., who explored the “basic tension” in small peptides between deprotonated amido nitrogens that bind to metals vs. the tautomeric, carboxy bound form …”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The synthetic paths to complex 5 emphasize metal exchange processes in intricate proton/metal competitions that are likely related to synthetic routes to metalloproteins and enzymes. Engagement of carboxamide oxygens as donor sites for zinc in peptide bioconjugates have been observed by the Alsfasser group, while Hahn et al., have reported a pH dependent, reversible switching of the N/O amide coordination modes in tripodal complexes of Zn II , Cu II , and Ni II . More closely related to our discovery are well‐designed studies via infrared multiple photon dissociation spectroscopy and DFT calculations from Dunbar et al., who explored the “basic tension” in small peptides between deprotonated amido nitrogens that bind to metals vs. the tautomeric, carboxy bound form …”
Section: Discussionsupporting
confidence: 51%
“…While the mimics of biological N 2 S 2 binding sites,i ncluding the ema ligand have been studied for decades,t his example of H 2 ema 2À as ab inucleating ligand is unknown or unreported until now.T he synthetic paths to complex 5 emphasize metal exchange processes in intricate proton/metal competitions that are likely related to synthetic routes to metalloproteins and enzymes.E ngagement of carboxamide oxygens as donor sites for zinc in peptide bioconjugates have been observed by the Alsfasser group, [16] while Hahn et al, have reported apHdependent, reversible switching of the N/ Oa mide coordination modes in tripodal complexes of Zn II , Cu II ,a nd Ni II . [17] More closely related to our discovery are well-designed studies via infrared multiple photon dissociation spectroscopy and DFT calculations from Dunbar et al, who explored the "basic tension" in small peptides between deprotonated amido nitrogens that bind to metals vs.t he tautomeric,carboxy bound form. [18] Theg reat stability of the dimanganese complex, yet with ligand exchange capability that implicates the likelihood of opening ac oordination site,o ffers an ew platform for examining bimetallic reactivity.The key factor that influences the folding of the free ligand is the preferred coordination environment of the targeting transition metal that promotes the iminol tautomer and lies at the center of the competition of metallation vs.protonation determining the folding behavior of Kruger, Peng, and Holmsema ligand.…”
Section: Resultsmentioning
confidence: 93%
“…While the mimics of biological N 2 S 2 binding sites,i ncluding the ema ligand have been studied for decades,t his example of H 2 ema 2À as ab inucleating ligand is unknown or unreported until now.T he synthetic paths to complex 5 emphasize metal exchange processes in intricate proton/metal competitions that are likely related to synthetic routes to metalloproteins and enzymes.E ngagement of carboxamide oxygens as donor sites for zinc in peptide bioconjugates have been observed by the Alsfasser group, [16] while Hahn et al, have reported apHdependent, reversible switching of the N/ Oa mide coordination modes in tripodal complexes of Zn II , Cu II ,a nd Ni II . [17] More closely related to our discovery are well-designed studies via infrared multiple photon dissociation spectroscopy and DFT calculations from Dunbar et al, who explored the "basic tension" in small peptides between deprotonated amido nitrogens that bind to metals vs.t he tautomeric,carboxy bound form. [18] Theg reat stability of the dimanganese complex, yet with ligand exchange capability that implicates the likelihood of opening ac oordination site,o ffers an ew platform for examining bimetallic reactivity.The key factor that influences the folding of the free ligand is the preferred coordination environment of the targeting transition metal that promotes the iminol tautomer and lies at the center of the competition of metallation vs.protonation determining the folding behavior of Kruger, Peng, and Holmsema ligand.…”
Section: Discussionmentioning
confidence: 93%